A Guide to Intracranial Bypass Suture - Ajmera, Sonia; Kvint, Svetlana; Graffeo, Christopher S.; Barbosa, Ronald R.; Srinivasan, Visish M. (Journal of Neurological Surgery Part B: Skull Base, 2025)
Introduction Cerebrovascular bypass surgery is technically demanding, with dozens of modifiable parameters influencing operative decision-making. Thoughtful selection of needle and suture materials is critical to success in these operations.Methods Based on the authors' experiences and existing literature, a brief guide to needle and suture selection is provided.Results Recommendations for needle and suture have taken into consideration key features of bypass constructs, such as bypass type, vessel caliber, and working space. Specific suture and needle are highlighted from two of the most common industry suppliers.Conclusion This guide synthesizes clinical insights and practical guidelines to support neurosurgical trainees and practitioners in mastering cerebrovascular bypass techniques.
Keywords: bypass; cerebrovascular; needle; microsurgery; suture